Waste-to-wealth: Energy pack as an integrated biofuel - Ng, W.P.Q. (Italian Association of Chemical Engineering - AIDIC, 2014)
The global trend is moving towards green energy generation and application. However, there exists a transition period where the usage of fossil fuel is unavoidable while green energy is being developed. A transitional level of fuel - Energy Pack is introduced. Energy Pack is an industrial waste oil integrated biofuel, which the existing biofuel is 'packed' with industrial oil for improved heating value. The feasibility of producing this transitional level of fuel is investigated and the energy potential of the product is studied. The integration of Energy Pack production process into the existing biofuel generation facilities is modelled and its energy performance is studied. Besides, the absorption correlation of industrial oil into the biofuel is studied. The physical elements and properties of Energy Pack are compared to the existing biofuels. In addition, the incineration impact of Energy Pack is investigated. The introduction of Energy Pack gives one solution to industrial waste management as well as improving the heating performance of the existing biofuel.. Copyright Â© 2014, AIDIC Servizi S.r.l.